A CORPUS-BASED STUDY OF REPORTING VERBS IN SHORT ESSAY - Denisa Nur Febriyanti; Susi Yuliawati (Direktorat Pendidikan dan Internasionalisasi, 2024)
The present research aims to analyze the use of reporting verbs in short essays written by undergraduate students of English major at a university in Indonesia. The study focuses on the frequency analysis of reporting verbs across four semantic categories, namely Argue verbs (e.g., argue, suggest, write, etc.), Find verbs (e.g., find, observe, discover, etc.), Show verbs (show, demonstrate, reveal, etc.) and Think verbs (e.g., think, assume, know, etc.). To achieve this, a mixed-method research design and a corpus-based approach are employed. The results show that the students predominantly use the Think verbs category, followed by Argue, Show, and Find verbs. It suggests that students may focus more on expressing their beliefs and opinions rather than providing evidence or confirming their claims. Moreover, the study highlights the implications of the finding, indicating that the overuse of verbs from the Think verbs category may indicate a lack of evidence-based reasoning in the students’ short essays.